1998
DOI: 10.1046/j.1365-2249.1998.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of soluble Fas/APO-1 (CD95) in patients with hepatocellular carcinoma

Abstract: SUMMARYFas (APO-1/CD95)-mediated apoptosis plays an important role in liver cell destruction in viral hepatitis. Using sandwich ELISA, we measured serum levels of soluble Fas (sFas) in patients with hepatocellular carcinoma (HCC) who were positive for hepatitis B surface antigen (HBsAg) or antihepatitis C virus (HCV) antibody. sFas levels were significantly higher in HCC patients (median 4·07 ng/ml; range 0·14-29·18 ng/ml) than levels in age-matched healthy donors (0·29 ng/ml; 0-4·90 ng/ ml) (P < 0·0001) and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 30 publications
5
56
0
2
Order By: Relevance
“…High levels of sFas have also been described in certain chronic liver diseases [20,21] . However, the effects on acute decompensation of chronic liver diseases are not yet known.…”
Section: Introductionmentioning
confidence: 97%
“…High levels of sFas have also been described in certain chronic liver diseases [20,21] . However, the effects on acute decompensation of chronic liver diseases are not yet known.…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies have also reported that serum sFas levels of patients with various malignancies including solid tumors 18,19) and hematopoietic malignancies 20,21) were elevated. Furthermore, a correlation of the serum sFas level with the prognosis of patients was observed in several studies.…”
mentioning
confidence: 98%
“…sFas binds to and neutralizes Fas ligand, thereby functionally antagonizing the Fas-Fas ligand pathway [6]. Recently serum sFas has been reported to be elevated in patients with malignant diseases including prostate cancer [7][8][9][10][11][12][13]. Patients diagnosed with prostate cancer have also been shown to have significantly higher levels of serum sFas than those with benign prostate hyperplasia [13].…”
mentioning
confidence: 99%